« Sa main contre tous, la main de tous contre lui » : la dissidence de Pierre Caroli à travers la Défense de Guillaume Farel (1545) - Mathilde Bernard (Les Dossiers du GRIHL)
The study of this work written by Calvin and attributed by the latter to Nicolas des Gallards allows to deal with the way Geneva fought by the debate against the dissidence – that of Pierre Caroli, apostate and relaps, an enemy of the inside. Calvin's eloquence annihilates the character by destroying its aura and by presenting its renunciation as the consequence of ostracism and not as a voluntary act.